Comparative and Analysis of Controllers in Three-Phase Three-Level Neutral Point Clamped PWM Rectifier for Power Quality Assessment - Abdul Wahid, Mohamad Zuhaili (2017)
In this study, two controllers: PI Controller (PIC) and Fuzzy Logic Controller (FLC) in Three-phase Three-level NPC PWM Rectifier used to improve the power quality. The controllers are applied to regulate the input current and the output voltage of the rectifier. The power quality assessment is made by analyzing the power factor (PF) and total harmonic distortion (THD) in this rectifier. The PF and THD can be analyzed from the result of simulation by using the PIC and FLC. The results of both controllers are compared to identify which controller will give the best performance for this assessment. It is found that PIC performs well giving more stable output voltage, Vdc with less oscillations, lower steady-state error and faster settling time compared to FLC. While FLC’s performance is slightly better in terms of PF regulation compared to PIC. The THD(s) generated based on PIC are lower than FLC which again shows that PIC performs better for this case.